2019
DOI: 10.1111/nph.16362
|View full text |Cite
|
Sign up to set email alerts
|

Roles of RIN and ethylene in tomato fruit ripening and ripening‐associated traits

Abstract: Summary RIPENING INHIBITOR (RIN)‐deficient fruits generated by CRISPR/Cas9 initiated partial ripening at a similar time to wild‐type (WT) fruits but only 10% WT concentrations of carotenoids and ethylene (ET) were synthesized. RIN‐deficient fruit never ripened completely, even when supplied with exogenous ET. The low amount of endogenous ET that they did produce was sufficient to enable ripening initiation and this could be suppressed by the ET perception inhibitor 1‐MCP. The reduced ET production by RIN‐def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 74 publications
6
137
0
Order By: Relevance
“…while, in tomato, JA influences polyamine levels and SlSAMT catalyzes the biosynthesis of SA into methyl salicylate to enhance the taste of ripe fruit (Tieman et al ., 2010; Kumar et al ., 2014). An exciting and currently expanding area of inquiry pertains to the genetic understanding of the accumulation of flavor and aroma volatiles (Tieman et al ., 2017; Gao et al ., 2019a, 2019b; Li et al ., 2020a, 2020b) and, while plant hormones likely play a role in their production, this is an area open to further exploration.…”
Section: Ripeningmentioning
confidence: 99%
“…while, in tomato, JA influences polyamine levels and SlSAMT catalyzes the biosynthesis of SA into methyl salicylate to enhance the taste of ripe fruit (Tieman et al ., 2010; Kumar et al ., 2014). An exciting and currently expanding area of inquiry pertains to the genetic understanding of the accumulation of flavor and aroma volatiles (Tieman et al ., 2017; Gao et al ., 2019a, 2019b; Li et al ., 2020a, 2020b) and, while plant hormones likely play a role in their production, this is an area open to further exploration.…”
Section: Ripeningmentioning
confidence: 99%
“…Our data show that the cell wall metabolism-related enzymes CEL2, EXP, XTH5, PG, and TBG4, the ethylene biosynthesis-related genes ACO1, ACO3, and ACS2, and the ethylene responsive genes E4 and E8 were all expressed at significantly higher levels in lcd1-7 than in wild-type tomato fruit. RIN, a MADS-box family transcription factor, and Nor, a NAC family transcription factor, are TFs that have been shown to be important in regulating ethylene biosynthesis and fruit ripening [26][27][28] . We found that the expression levels of RIN and Nor increased significantly at the beginning of fruit ripening in WT tomato, but significantly higher gene expression was found in lcd1.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference of SlACS2 in tomato fruits repressed ethylene production and fruit ripening [ 39 ]. Additionally, RIPENING INHIBITOR (RIN) and ethylene, via ethylene response factors (ERFs), are required for the complete expression of ripening genes such as E4 and E8 , the classic ethylene-induced genes [ 8 ]. ERFs regulate ethylene-dependent transcription and ethylene-inducible gene expression that play an important role in ripening [ 5 , 7 , 38 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naeem et al identified that SmCOP1 (CONSTITUTIVE PHOTOMORPHOGENIC) regulates ethylene biosynthesis and affects fruit ripening in tomato [ 4 ]. Studies have also shown that ethylene triggers fruit ripening via the ethylene signaling pathway [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%